2019
DOI: 10.1016/j.jclepro.2019.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Symbiosis: towards a design process for eco-industrial clusters by integrating Circular Economy and Industrial Ecology perspectives

Abstract: Industrial Symbiosis (IS) is a collective approach to competitive advantage in which separate industries create a cooperative network to exchange materials, energy, water and/or by-products. By addressing issues related to resource depletion, waste management and pollution, IS plays an important role in the transition towards sustainable development. In the literature, two conceptual perspectives on IS can be identified: the Industrial Ecology (IE) and the Circular Economy (CE) perspective. Despite the recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(171 citation statements)
references
References 49 publications
1
134
0
10
Order By: Relevance
“…For example, Spokas et al () point out that the development of biochar has been facilitated by previous research experiences in biomass. Moreover, Lieder and Rashid () and Baldassarre et al () point out that the development of sustainable processes in firms, such as the application of integrated management systems (ISO, ), or the application of Directive 2009/125/EC, for the establishment of ecodesign requirements for energy‐related products, or industrial symbiosis processes, in the context of circular economy, have been facilitated in their implementation by previous eco‐innovations of process and organisation such as the ISO 9001. Therefore, the eco‐innovation process needs the generation of firms' capabilities, including the development of tasks, routines, and teams in the firm.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Spokas et al () point out that the development of biochar has been facilitated by previous research experiences in biomass. Moreover, Lieder and Rashid () and Baldassarre et al () point out that the development of sustainable processes in firms, such as the application of integrated management systems (ISO, ), or the application of Directive 2009/125/EC, for the establishment of ecodesign requirements for energy‐related products, or industrial symbiosis processes, in the context of circular economy, have been facilitated in their implementation by previous eco‐innovations of process and organisation such as the ISO 9001. Therefore, the eco‐innovation process needs the generation of firms' capabilities, including the development of tasks, routines, and teams in the firm.…”
Section: Hypothesesmentioning
confidence: 99%
“…For example, Spokas et al (2012) point out that the development of biochar has been facilitated by previous research experiences in biomass. Moreover, Lieder and Rashid (2016) and Baldassarre et al (2019) Doran (2012) points out that the interrelation between capabilities arises as a consequence of the need to develop tasks and the affinity between them. In this sense, Hullova, Trott, and Simms (2016) study interactions among technological innovations and classify them according to two dimensions: first by the order of interaction, which can be simultaneous or sequential; and second, by the degree of interaction, which can be synergistic or complementary.…”
Section: Persistence Over Time Of Eco-innovationmentioning
confidence: 99%
“…Since 1998 and Elkington's statement, known as the "triple bottom line" concept, new conceptual entities have been suggested both describing and evolving sustainable development holistically. Indicatively, the concepts of "circular economy" (Geissdoerfer, Savaget, Bocken, & Hultink, 2017;Ghisellini, Cialani, & Ulgiati, 2016;Kirchherr, Reike, & Hekkert, 2017), "industrial symbiosis" (Baldassarre et al, 2019;Boons, Spekkink, & Mouzakitis, 2011;Chertow, 2008;Lombardi & Laybourn 2012), "Circles of Sustainability and the Fourth Dimension" (Hobson, 2015;Hopwood, Mellor, & O'Brien, 2005;Maydl, 2006;Robinson, 2004), and the "seven modalities" model (Murphy & McDonagh, 2016) have dynamically entered the academic and business world.…”
Section: Defining Csr and Sustainabilitymentioning
confidence: 99%
“…Furthermore, data from literature was used for the validation of the LCA of the industrial symbiosis with insect farming, particularly Marchi et al [58], Smetana et al [59] and Halloran et al [49]. Industrial symbiosis was identified in the scientific and institutional literature as a core concept for the implementation of a circular economy; for instance, by Taranic et al [25], Cui & Lui [26], and Baldassarre et al [27]. The Circular Economy Action Plan of the EU urges the promotion of innovative industrial processes including industrial symbiosis.…”
Section: Sharing Resources Through Industrial Symbiosismentioning
confidence: 99%
“…Industrial symbiosis describes a business collaboration wherein residuals from one enterprise serve as inputs to another [23]. It was characterized as a core concept for the implementation of circular economy according to McDonough & Braungart [24] in scientific and institutional literature (for instance [25][26][27]). In addition, the Circular Economy Action Plan of the EU urges to promote innovative industrial processes, including industrial symbiosis.…”
Section: Introductionmentioning
confidence: 99%